(untitled) (Research, Society and Development, 2023)
Averrhoa carambola L. is widely distributed and cultivated in tropical countries. It is believed that the fruit has intense Averrhoa carambola L. is widely distributed and cultivated in tropical countries. It is believed that the fruit has intense secondary metabolic activity and may present multiple bioactivities, such as: antihyperglycemic, antiobesity, antihyperlipidemic, hepatoprotective, cardioprotective, antihypertensive and neuroprotective. Thus, the objective of this work was to analyze, through the literature, the phytochemical and toxicological profile of the fruits of Averrhoa carambola L. This is an integrative review, including all the complete literature, in English and Portuguese, in the period from 2012 to 2021. Guidelines, pre prints, paid articles and duplicates were excluded. The literature that composed the review is from the SciELO, MEDLINE and LILAC databases of higher level repositories. Ten literature were eligible for this review, of which – 70% (7) in SciELO; 20% (2) in MEDLINE and 10% (1) in LILACS, of which 50% (5) are in English and 50% (5) in Portuguese. A. carambola L can act as an enzyme inhibitor or potentiator and interfere in processes related to hemostatic balance: coagulation; thrombus dissolution and fibrinogenolysis; it has flavonoids and tannins and its popular use can really bring benefits to the health of the population, but it can have nephrotoxic and neurotoxic effects for chronic kidney patients.